Reconstruction of the Constitutional Law Post-Covid-19 Emergency - Anwar Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to identify and describe changes in constitutional law as a form of conformity in the post-Covid-19 emergency situation, especially in Indonesia. The method used in this research is descriptive qualitative. The data collection technique used a literature study in the form of a documentation study. The data analysis method uses qualitative analysis which is then directed to draw a conclusion using deductive thinking methods. The results show that the post-Covid-19 Emergency Constitutional Law has a lot to do with economic recovery efforts from the socio-economic impacts caused by the Covid-19 pandemic since the beginning of 2020. In 2022, since the decline in the positivity rate in Under WHO standards, Indonesia has begun to implement so many policies related to national economic recovery such as accelerating government spending, relaxing income taxes, and restoring the national economy by implementing state financial policies through the relaxation of the state budget.